Process‐based models are required to manage ecological systems in a changing world. Issue 2 (8th February 2013) - Cuddington, K.; Fortin, M.-J.; Gerber, L. R.; Hastings, A.; Liebhold, A.; O'Connor, M.; Ray, C.
Abstract : Several modeling approaches can be used to guide management decisions. However, some approaches are better fitted than others to address the problem of prediction under global change. Process‐based models, which are based on a theoretical understanding of relevant ecological processes, provide a useful framework to incorporate specific responses to altered environmental conditions. As a result, these models can offer significant advantages in predicting the effects of global change as compared to purely statistical or rule‐based models based on previously collected data. Process‐based models also offer more explicitly stated assumptions and easier interpretation than detailed simulation models. We provide guidelines for identifying the appropriate type of model and level of complexity for management decisions. Finally we outline some of those factors that make modeling for local and regional management under global change a particular challenge: changes to relevant scales and processes, additional sources of uncertainty, legacy effects, threshold dynamics, and socio‐economic impacts.